Soft template-assisted copper-doped sodium dititanate nanosheet/graphene oxide heterostructure for photoreduction of carbon dioxide to liquid fuels - Napat Lertthanaphol; Natthanicha Prawiset; Pornpinun Soontornapaluk; Nutkamol Kitjanukit; Wannisa Neamsung; Natpichan Pienutsa; Kittapas Chusri; Thirawit Sornsuchat; Prowpatchara Chanthara; Poomiwat Phadungbut; Panpailin Seeharaj; Pattaraporn Kim-Lohsoontorn; et al. (My University, 2022)
The copper-doped sodium dititanate nanosheets/graphene oxide heterostructure (CTGN) was synthesized following a one-step hydrothermal process, exhibiting an outstanding photoactivity in converting CO 2 to acetone, methanol, ethanol and i-propanol.
Keywords: Nanosheet; Copper oxide; Carbon fibers; Advanced Photocatalysis Techniques